Unexpected adhesive bowel obstruction after endoscopic submucosal dissection of early sigmoid colon cancer - Kenta Seki; Taku Sakamoto; Mai Ego Makiguchi; Naoya Toyoshima; Hiroyuki Takamaru; Masau Sekiguchi; Masayoshi Yamada; Shigeki Sekine; Yukihide Kanemitsu; Yutaka Saito (DEN Open, 2023)
Abstract Various complications of colorectal endoscopic submucosal dissection (ESD) have been reported, including bleeding, penetration, perforation, and coagulation syndrome. However, the occurrence of bowel obstruction after ESD is rare. We report a case of adhesive bowel obstruction after ESD for a laterally spreading tumor in the sigmoid colon. The 35‐mm tumor was successfully removed by ESD without intraoperative complications. The patient had a fever, lower abdominal pain, and a small amount of bloody stool the day after ESD. Endoscopy revealed minor bleeding from the ESD scar, which was treated by hemostatic clips. Pathological analysis showed adenocarcinoma was exposed to the vertical margin; therefore, the resection was non‐curative. At 39 days after ESD and 36 days after discharge, the patient had abdominal pain and nausea. She was readmitted with a diagnosis of adhesive bowel obstruction. Conservative treatment was ineffective; therefore, she underwent sigmoidectomy combined with partial resection of the small intestine because of small intestinal stenosis caused by inflammation. The pathological examination showed localized peritonitis around the sigmoid colon where ESD was performed. There was more fibrosis along the serous surface of the small intestine than on the sigmoid colon. We concluded that there was a micro‐perforation that could not be detected by endoscopy or physical examination. This case indicates that adhesive bowel obstruction may occur as a complication of ESD.